Analysis of Indonesia's Fiscal Policy Strategy in Compiling State Revenue and Expenditures - Faruq, Assad Al (Journal of Economics and Social Sciences (JESS), 2023)
Introduction/Main Objectives: This study aims to analyze Indonesia's fiscal policy strategy in regulating state revenues and expenditures in 2020. Research Methods: The method used in this study is a library research methodology using a qualitative approach. A qualitative approach is taken to produce a more in-depth description of the writing, description, and explanation of an event's substance. Finding/Results: The results of the data analysis show that several fiscal policy strategies can regulate state revenues and expenditures in Indonesia in 2020, namely the strategy of maximizing tax revenues and the relaxation-participation strategy. On the expenditure side, the government will revise the budget to emphasize the state budget deficit figure to help finance the government. Conclusion: Fiscal policy is essential for the country's economy because it can move it. So that the government must be able to make the right policies so that the community's economy increases.